Compressive Strength Characteristics of Mortar Composite Materials Influenced by the Fly Ash Mass Composition Ratio - Muhammad Yusuf Rahmansyah Siahaan; Siregar, Rakhmad Arief; Faisal Amri Tanjung; Muhammad Nuh Hudawi Pasaribu (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2025)
The application of science and technology to mortar composite materials creates increasingly better economic value advantages and its development potential has a positive impact on the field of building construction with the implementation of household appliances, coral transplant media, sea walls, roads, curbs, paving blocks, reclaimed land, plant vases, wall ornaments, and acoustic panels. Fly ash material as industrial waste has been categorized as non-B3 waste by the government so that the use of Fly Ash can be optimized to maintain environmental sustainability and become a catalyst for driving the community's economy. This study with a 1: 2 ratio mortar material added with fly ash material to analyze the mechanical properties of the material using experimental testing methods on 3 variations of fly ash material compositions in sequence 10%, 30%, and 50% aims to obtain compressive strength characteristics and mass percentage. The test results provide the highest compressive strength value data on 10% fly ash material of 28.10 MPa while other composition variations tend to show a decrease in the ability of material resilience properties in sequence of 9.36% and 20.32%. The mechanical properties of compressive strength meet the quality requirements of SNI 03-0691-1996 for implementation on paving blocks of type B quality and SNI 2442-2020 for application on concrete curbs. The influence of mass composition provides a positive contribution creating an increasing trend towards the mass percentage where the response of fly ash variations is respectively 20.74% and 14.33%.